A state‐of‐the‐art review of the experience of care coordination interventions for people living with multimorbidity. Issue 9 (27th February 2020) - Peart, Annette; Barton, Chris; Lewis, Virginia; Russell, Grant
Abstract: Aim: To explore recent research on care coordination interventions for people living with multimorbidity, from the perspective of the person receiving care. Background: Care coordination interventions for people living with multimorbidity show some effectiveness in improving management of their health and reducing potentially preventable hospitalisations. The experience of people enrolled in care coordination interventions requires further exploration. Design: State‐of‐the‐art review. Methods: A review was guided by the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) checklist where five databases (The Cochrane Library, PsycINFO, Scopus, CINAHL and MEDLINE) were searched for qualitative sources published from January 2008–March 2019. Two additional databases focused on multimorbidity and integrated care were included in the search. Titles, abstracts and full texts were screened using inclusion criteria. Reference lists of the included articles were hand‐searched. Summary tables were developed for data extraction, and the data were mapped to the research question. Results: Eighteen primary research articles were included. Three themes of participant experience were identified: (a) relationships built on trust, (b), a sense of safety and security and (c) feeling cared for and respected. Conclusion: The contribution of qualitative approaches to evaluating the experiences of care for people living with multimorbidity is growing. Participants' describe a focus on relationships formed with healthcare professionals during care coordination. Further research incorporating lived experiences of participants could illuminate these concepts further. Relevance to clinical practice: People living with multimorbidity who require assistance via care coordination value trusting relationships with healthcare professionals, who respect their needs and provide a sense of security. Understanding participant experiences is important to shape care coordination interventions that incorporate person‐centred approaches.